Customary law marriages in Kenya – current legal status and evaluation of value system entailed - Dr Wathuta, Jane; Deche, Fadhili (Strathmore University, 2019)
This paper seeks to highlight the broad distinguishing features of certain types of customary marriages in Kenya. It outlines their current legal status, and identifies and evaluates the value system they entail. These marriage practices span the pre-colonial, colonial and post-independence periods, and are regulated by the 2010 Constitution, the Marriage Act of 2014, and the Judicature Act (2016 version). Customary lawmarriages tend to be narrowly identified with their potential or actual polygamous nature, and the obligatory payment of bride price as a condition for their cultural (and legal) validity. Recent legal developments, furthermore, require their formal notification and registration, on given conditions, which, although advantageous in certain aspects, also compounds some existing dilemmas and raises new ones. Using secondary data, this paper identifies and studies the various components of the customary marriage system in Kenya. The underlying values are then evaluated, using a philosophical and social science evidence base that brings to the fore the individual and public good resulting from the institution of marriage. The current statutory requirements should be understood as going beyond the legalisation and possible instrumentalisation of customary law marriages. Instead, the implicit acknowledgement of the value system entailed could be regarded as a step in the direction of safeguarding the integrity of legitimate customary perspectives regarding marriage, thereby contributing to the individual and public good.
Rsearch Brown Bag Presentations